AN IN VIVO EVALUATION OF THE INFLAMMATORY EFFECT OF PURIFIED COMEDONAL COMPONENTS IN HUMAN SKIN - Madli Puhvel, S.; Sakamoto, Midori (Journal of investigative dermatology, 1977)
Leakage of intrafollicular material from closed comedones is thought to induce the perifollicular inflammation in acne. Previously free fatty acids (FFA) were implicated as the incendiary factors in comedones, but recent studies have disputed this (J invest Dermatol 68:93–97, 1977). The present investigation reevaluated the inflammatory effect of intradermal injection of different comedonal fractions in amounts which approximate the levels present in comedones. The following substances were injected in 0.03ml of saline into 29 volunteers (16 with acne, 13 acne-free): 500 μg of skin surface lipids (SSL), 200 μg of FFA, 50 μg of squalene, 2 × 105 Propionibacterium acnes. 1 × 105 Staphylocuccus epidermidis. 0.7 μg of P. acnes cell walls, 60 μg of water-soluble comedonal extract, and 30 μg of comedonal insoluble keratinous material. Of all comedonal components tested, insoluble keratinous material was most uniformly inflammatory in all subjects. Reactions to P. acnes were consistently more severe in subjects with acne compared to acne-free controls and it made no difference whether the injected organisms were viable or heat killed. Water-soluble extracts of comedones induced inflammatory response in most subjects, but SSL, FFA, and squalene did not produce visible inflammation in any subject tested. Addition of 300 μg of SSL to suspensions of 2 × 105 P. acnes intensified the inflammatory effect of the organisms. These observations suggest that sebaceous lipids per se are not the inflammatory agents in acne. The effect of antibiotics in acne is more likely to depend on direct suppression of P. aenes as inflammatory agents, rather than on the indirect reduction of intrafollicular lipases as the free fatty acid theory of acne pathogenesis had previously supposed.